Online Games and English as a Foreign Language Vocabulary Learning Among Eighth-Grade Students - Talia Soledad Cuenca-Calva; Bertha Lucia Ramón-Rodríguez; Miriam Eucevia Troya-Sánchez (Journal of English as A Foreign Language Teaching and Research, 2024)
The limited vocabulary knowledge of eighth-grade students from a public institution in Loja inhibits the proper development of English skills. The present research aimed to increase vocabulary knowledge through the implementation of online games among eighth-grade students between 12 and 13 years old at a public institution in Loja, Ecuador. The investigation employed a mixed method following a practical action research model through five stages; initial reflection, planning, action, observation, and reflection, with the participation of 25 Ecuadorian eighth graders chosen by purposeful sampling. Pre- and post-tests, questionnaires, reflective journals, and peer observations collected both quantitative and qualitative data. The pretest and posttest measured students’ knowledge about their vocabulary, whereas the other instruments attempted to describe students’ perceptions regarding the use of online games to learn vocabulary. Quantitative information was analyzed through descriptive statistics and qualitative information through a thematic analysis. The results showed a difference of 3.07 points between the pretest and posttest, which denoted a significant increase in the knowledge of various aspects of vocabulary such as form, meaning, and use. Moreover, eighth graders perceived the online games; Educandy, Genially, Vocabulary Spelling City, Wordwall, and especially Blooket, as innovative and fun educational resources that increased their motivation and active participation while acquiring new vocabulary. Hence, it was concluded that online games were effective in improving vocabulary because they created a dynamic educational environment. This study contributes to the educational field by highlighting new digital tools to improve English language proficiency.